2014
DOI: 10.4236/health.2014.610123
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase: Therapeutic Targets in SOD Related Pathology

Abstract: There are growing evidences on the role of adaptive mechanisms of all cell types in pathological processes: atherosclerosis, ischemic attack, bacterial infections, etc. All kinds of these processes involve as main mechanism oxidative stress. Aerobic organisms use oxygen in processes that accidentally or deliberately generate aggressive species for the biologic components in the form of radicals. Radicals were looked initially as "harmful" molecules and this is true for large quantities but in small or even mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
(76 reference statements)
0
6
0
1
Order By: Relevance
“…Oxidative stress generated during rotenone intoxication as observed in this study could arise from metabolic consequence of mitochondrial dysfunction and incomplete glucose oxidation. More hydrogen peroxide is also produced when purines are been broke down to uric acid in the cell by XO (Cristiana et al, 2014). The free radical produced leads to oxidative damage that caused protein carbonylation and consequently attacks membrane lipid.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress generated during rotenone intoxication as observed in this study could arise from metabolic consequence of mitochondrial dysfunction and incomplete glucose oxidation. More hydrogen peroxide is also produced when purines are been broke down to uric acid in the cell by XO (Cristiana et al, 2014). The free radical produced leads to oxidative damage that caused protein carbonylation and consequently attacks membrane lipid.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the activity of antioxidant enzymes like SOD can decrease levels of lipid peroxides acting as free radicals. SOD can also convert the free radical anion superoxide (2O 2 (11,32,34,35). Meanwhile, Mohebbi et al (36) reported that increased SOD activity was followed by an increase in glutathione peroxidase (GSPHx) enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…The superoxide radical has an unpaired electron within its orbital; the unpaired electron creates a reactive compound capable of producing oxidative damage [2,3]. …”
Section: Figurementioning
confidence: 99%
“…A free radical, for the purpose of this review, is defined as a compound that has one or more unpaired electrons in its orbital and is capable of finite existence (Figure 1) and includes superoxide [2,3]. Free radicals have extremely high chemical reactivity, which can in turn cause damage to cells.…”
Section: Introductionmentioning
confidence: 99%